Impact of chronic obstructive pulmonary disease on clinical course after an episode of acute heart failure. EAHFE–COPD study. (15th January 2017) - Jacob, Javier; Tost, Josep; Miró, Òscar; Herrero, Pablo; Martín-Sánchez, Francisco Javier; Llorens, Pere; ,
Abstract: Objective: To study if the coexistence of chronic obstructive pulmonary disease (COPD) in patients diagnosed with acute heart failure (AHF) at the emergency department (ED) has an impact on short- and long-term outcomes. Method: The EAHFE–COPD study included patients who attended in 34 Spanish EDs for AHF. We compared patients with AHF plus COPD with patients with AHF in whom COPD was neither diagnosed nor excluded by functional respiratory tests (FRT). Outcome analysis included all-cause mortality, prolonged hospitalization, and ED revisit. Crude results were adjusted by differences between patients with and without COPD. Results: We included 8099 patients with AHF, 2069 having COPD (25.6%; AHF-COPD-known). Compared with AHF-COPD-unknown, AHF-COPD-known differed in 20 variables. After adjusting for differences between the two groups, AHF-COPD-known patients showed no significant differences in 30-day mortality (OR = 0.89; 95% CI = 0.71–1.11), prolonged hospitalization in general wards (OR = 1.04; 95% CI = 0.89–1.22) or SSU (OR = 1.38; 95% CI = 0.97–1.97), and 1-year mortality (HR: 1.02; 95% CI = 0.89–1.17), but showed a higher 30-day revisit rate (OR = 1.32; 95% CI = 1.13–1.54). Conclusions: In patients attending the ED for AHF, the coexistence of COPD is only associated with an increased risk of short-term ED revisit, but not prolonged hospitalization and short- or long-term mortality.